Forced-Air Warming and Resistive Heating Devices. Updated Perspectives on Safety and Surgical Site Infections - Ackermann, Wiebke; Fan, Qianqian; Parekh, Akarsh J.; Stoicea, Nicoleta; Ryan, John; Bergese, Sergio D. (Frontiers in Surgery, 2018)
Introduction: Perioperative hypothermia is one of the most common phenomena seen among surgical patients, leading to numerous adverse outcomes such as intraoperative blood loss, cardiac events, coagulopathy, increased hospital stay and associated costs. Forced air warming (FAW) and resistive heating (RH) are the two most commonly used and widely studied devices to prevent perioperative hypothermia. The effect of FAW on operating room laminar flow and surgical site infection is unclear and we initiated an extensive literature search in order to get a scientific insight of this aspect. Material and Methods: The literature search was conducted using the Medline search engine, PubMed, Cochrane review, google scholar, and OSU library. Results: Out of 92 Articles considered initially for review we selected a total of 73 relevant references. Currently there is no robust evidence to support that FAW can increase SSIs. In addition, both of the two warming devices present safety problems. Conclusion: As unbiased independent reviewers, we advise clinicians to weigh the risks and benefits when using either one of these devices; no change in the current practice is necessary until further data emerges.